2011
DOI: 10.1094/phyto-09-10-0255
|View full text |Cite
|
Sign up to set email alerts
|

Control of Postharvest Botrytis Fruit Rot of Strawberry by Volatile Organic Compounds of Candida intermedia

et al.

Abstract: A study was conducted to identify volatile organic compounds or volatiles produced by Candida intermedia strain C410 using gas chromatography-mass spectrometry, and to determine efficacy of the volatiles of C. intermedia in suppression of conidial germination and mycelial growth of Botrytis cinerea and control of Botrytis fruit rot of strawberry. Results showed that, among 49 volatiles (esters, alcohols, alkenes, alkanes, alkynes, organic acids, ketones, and aldehydes) identified from C. intermedia cultures on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(150 citation statements)
references
References 51 publications
6
137
0
7
Order By: Relevance
“…The VOCs with highly inhibitory capability towards conidial germination and mycelia growth included phenylethyl alcohol and caryophyllene. 2-nonanone has been identified from the volatiles produced by C. intermedia strain to control postharvest disease of strawberry (Huang et al, 2011) and thymol was applied as the essential oil to inhibit fruit rot fungi (Ippolito et al, 2012). Our results demonstrated that in addition to 2-nonanone and thymol, other bioactive volatile compounds including 2-decanone, 2-methylpyrazine and b-benzeneethanamine produced by the two isolated strains also have antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VOCs with highly inhibitory capability towards conidial germination and mycelia growth included phenylethyl alcohol and caryophyllene. 2-nonanone has been identified from the volatiles produced by C. intermedia strain to control postharvest disease of strawberry (Huang et al, 2011) and thymol was applied as the essential oil to inhibit fruit rot fungi (Ippolito et al, 2012). Our results demonstrated that in addition to 2-nonanone and thymol, other bioactive volatile compounds including 2-decanone, 2-methylpyrazine and b-benzeneethanamine produced by the two isolated strains also have antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…(M-7), a thermophilic soil bacterium, can produce VOCs which have the biological activity against a series of fungal pathogens, such as Aspergillus fumigatus, Geotrichum candidum, Sclerotinia sclerotiorum, Trichoderma viride, Botrytis cinerea, and Verticillium dahliae (Ren et al, 2010). Other examples of biological control agents include, Bacillus strains for black spot of citrus (Arrebola et al 2010),-ce:italic>Streptomyces globispourous against B. cinerea on tomato fruit (Li et al, 2012), and Candida intermedia for postharvest diseases of strawberry (Huang et al, 2011). However, limited research information is available related to the efficacy of biofumigation volatiles for the control of mango anthracnose pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…cinerea , and S . sclerotiorum , disease severity on the strawberries was individually rated using a numeric scale from 0 (completely healthy) to 8 (completely rotten) according to the description by Huang et al (2011). Disease severity index (DSI) was then calculated using the following formula: DSI =100 ×i = 0n(Sn× n)/8 × i = 0n(Sn) …”
Section: Methodsmentioning
confidence: 99%
“…The cell-free culture filtrate (100 µL) was mixed with 900 μL of 0.1 M Sodium Acetate Buffer, pH 5.5, and supplemented with colloidal chitin (10 g/L). Colloidal chitin was prepared from shrimp shell chitin according to the methods provided by Roberts and Selitrennikoff (1988) and Zhang et al (2011). Enzyme-substrate mixtures were incubated in a water bath at 37 °C for 7 h under shaking.…”
Section: 32-chitinase and Laminarinase Activitiesmentioning
confidence: 99%
“…Production of antifungal volatiles was assayed as described by Huang et al (2011) with some modifications. The ability of yeasts to produce antifungal volatiles was assayed in a sealed system, but the phytopathogenic fungus and its respective biocontrol yeast were not in physical contact.…”
Section: 33-antifungal Volatilesmentioning
confidence: 99%